2023
DOI: 10.1039/d3dt00298e
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic alkyl(amino)iminates (CAAIs) as strong 2σ,4π-electron donor ligands for the stabilisation of boranes and diboranes(4): a synthetic and computational study

Abstract: Singly and doubly cyclic alkyl(amino)iminate (CAAI)-substituted boranes and diboranes(4) were synthesised by halosilane elimination between a silylimine and halo(di)borane precursors. 11B NMR-spectroscopic studies show that the CAAI ligand is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…We recently demonstrated that an acyclic carbene bearing two strongly donating N-heterocyclic imine (NHI) 8,31,32 substituents features exceptional nucleophilicity, enabling the dearomatization of a proximal inert arene ring 7 . We reasoned that the electron-rich nature of the bis(imino)carbene, coupled with its flexible acyclic framework is an ideal platform to access a doubly oxidized carbene.…”
mentioning
confidence: 99%
“…We recently demonstrated that an acyclic carbene bearing two strongly donating N-heterocyclic imine (NHI) 8,31,32 substituents features exceptional nucleophilicity, enabling the dearomatization of a proximal inert arene ring 7 . We reasoned that the electron-rich nature of the bis(imino)carbene, coupled with its flexible acyclic framework is an ideal platform to access a doubly oxidized carbene.…”
mentioning
confidence: 99%